Developing climate change adaptation strategies in building designs an assessment on the existing housing programs and morphology of vernacular and informal settlements in Cateel, Davao Oriental - Golimlim, Aprille Dawn L. (2019)
The Philippines is uniquely located at the circum-Pacific ring of fire, one of the most prone countries to natural disasters and climatic phenomenon that includes volcanic eruptions, earthquakes, and typhoons. In fact, it ranked 3rd of most climate vulnerable of among 15 countries worldwide with high exposure (52.46%), and high risk (27.69%) and 5th in Asia in housing loss during disaster as assessed by WRI in 2017. One of the contributors of the presented percentage are the frequent occurrence of approximately 20 typhoons per year and annual events of droughts and floods brought by to El Nino and La Nina. In 2012, typhoon Pablo have severely hit the municipality of Cateel in Davao Oriental which partially and totally damaged 10, 000 houses. With response to this need, there were housing and relocation projects provided by government, aid agencies, private, and non-government organization. Nevertheless, it was observed that incremental, modifications, or complete constructions of new houses were done by the beneficiaries in response to their growing number of family or climate change adaptation strategies. This paper assesses the existing housing programs in the location and aimed identify local climate events and adaption in housing design. The results of the study shows that of unexpected strong typhoons, landslide, flooding, stronger winds during amihan, unpredictable weather, longer rains and longer sunny days are the common existing climate events in the area. While the common adaptation strategies used by the settlers are stilts, using abono, making canal for drainage, and raised concrete flooring for flooding; using of used tires and woods for additional roof weight, and tying of roof to trees for high velocity wind; and extending balcony, change of house material, and planting trees or shrubs for high temperature. To follow the National Building Code of the Philippines and contribute to SDG 11: Sustainable Cities and Communities, the study primarily aimed to develop climate change adaptation strategies on building designs that will also consider the morphology of vernacular and informal settlements that may be used as reference and help other regions in the Philippines that are usually affected by natural calamities in developing adaptive measures in building designs.